The effect of AMPD1 genotype on blood flow response to sprint exercise - Norman, Barbara; Nygren, Anders T.; Nowak, Jacek; Sabina, Richard L. (European journal of applied physiology, 2008)
Inherited deficiency of skeletal muscle myoadenylate deaminase (mAMPD) is a genetic disorder characterized primarily by a 34C>T transition in exon 2 of the AMPD1 gene. mAMPD deficient individuals exhibit alterations in ATP catabolic flow, resulting in greater adenosine accumulation during high intensity exercise that may possibly enhance exercise-induced hyperaemia. This study tested the hypothesis that individuals with diminished mAMPD activity due to mutations in the AMPD1 gene develop a greater and faster blood flow response to high intensity exercise than individuals with two AMPD1 normal alleles (NN). Four 34C>T homozygotes, two compound heterozygotes (34C>T in one allele and a recently identified 404delT mutation in the other AMPD1 allele), collectively termed MM, one 34C>T heterozygote (NM) and eight NN males were studied. They performed a 30 s Wingate cycling test with monitoring of power output and other parameters of exercise performance. Common femoral artery blood flow was measured before and after (up to 25 min) exercise, using ultrasonography. Mean power during Wingate cycling was approximately 10% lower in MM/NM than in NN; p < 0.01. Blood flow response to exercise also differed between MM/NM and NN individuals (ANOVA; p < 0.001). There was also a difference in peak post-exercise blood flow ( p < 0.05), and the subsequent fall in blood flow during the recovery phase (T1/2) occurred more than twice as fast in MM/NM compared to NN subjects (7.8 ± 1.1 min vs. 16.1 ± 1.4 min, p < 0.001). These results suggest a better circulatory adaptation to exercise in individuals with diminished mAMPD activity, probably due to an AMPD1 genotype-dependent increase in adenosine formation.